Analysis of development inclusivity on extreme poverty: case in north maluku - Husen, Amran; Runtunuwu, Prince Charles Heston; Umar, Nyong; Marlon, Marlon (Institute of Computer Science (IOCS), 2024)
Indonesia experienced an increase in extreme poverty during the Covid-19 pandemic, rising from 9.22% in 2019 to 10.14% in 2020. In response to the target of reducing extreme poverty to 0% by 2024, Presidential Instruction Number 4 of 2022 on the Acceleration of Extreme Poverty Eradication was issued as the foundation for cooperation among policymakers at both the central and regional levels. The 2020-2024 Regional Medium-Term Development Plan (RPJMD) targets a reduction in the poverty rate in North Maluku to 6.19%. In reality, the poverty rate in North Maluku Province reached 6.39% in 2022, while in 2023, the poverty rate decreased to 6.25%. This indicates that the target set in the RPJMD is unlikely to be achieved, as 2024 is the final year of the current government’s term. The purpose of this study is to analyze the impact of economic growth, employment opportunities, the availability of economic infrastructure, human capital (HR), and financial inclusion on extreme poverty in the districts and cities of North Maluku. This study employs a quantitative analysis method (Structural Equation Modeling). The results of the study provide sufficient evidence that financial inclusion acts as a mediating variable in the relationship between employment opportunities, economic infrastructure, HR capacity, and basic infrastructure, which all have a significant positive impact on extreme poverty. Based on the findings, it is strongly explained that high economic growth in North Maluku Province does not significantly reduce extreme poverty